PENGARUH KEPEMIMPINAN, KOMPETENSI, DAN PELATIHAN, PEMBERDAYAAN TERHADAP KEPUASAN KERJA SERTA IMPLIKASI PADA KINERJA TTLM PUSKESMAS DI WILAYAH BANDUNG - Nany Djuhriah; Azhar Affandi; Erni Rusyani (Poltekkes Kemenkes Bandung, 2025)
Indonesia's national health system aims to improve public health through integrated and mutually supportive management. Puskesmas play an important role in this health system, especially in providing first-level health services, which include promotive and preventive aspects. Medical Laboratory Technologists (TTLM) support diagnosis and treatment at Puskesmas through medical laboratory analysis. This study aims to examine the influence of leadership functions, competence, training, and empowerment on job satisfaction and performance of TTLMs at puskesmas across the Bandung Metropolitan area. The method used in this research is a quantitative approach with SEM (Structural Equation Modeling) analysis. The sampling technique in this study is proportional stratified random sampling with 225 TTLMs with the inclusion criteria of TTLMs who have sufficient work experience in their fields and the exclusion criteria of TTLMs who are on sabbatical, have retired, or are not actively working during the study period are excluded; TTLMs with less than one year of service are also excluded; TTLMs who are not willing to fill out questionnaires or provide data; and TTLMs who work in the Bandung Metropolitan Health Center area. The results showed that leadership function, competence, training, and empowerment simultaneously significantly affected TTLM job satisfaction by 77.17%, with a significant effect on TTLM job satisfaction